Performance Affects - Thompson, J. author. aut Link
XIII, 205 p.
Keywords: Performance Affects explores performance projects in disaster and war zones to argue that joy, beauty and celebration should be the inspiration for the politics of community-based or participatory performance practice, seeking to realign the field of Applied Theatre away from effects towards an affective role, connected to sensations of pleasure.